دراسة ترجمة الآيات المتشابهات لصفات الله في "تفسير فيمفينن الرحمن" من منظور نظريتي الترجمة لنيومارك وفيني وداربلني - Lubna Abd Rahman; Muhammad Syafif Faiz; Arnida A. Bakar (Universiti Sains Islam Malaysia, 2026)
>آيات الصفات نوع من أنواع آيات المتشابهات، وهي التي يتضح بها المقصود ويحتمل تأويلها أكثر من معنى، وينبغي معرفة الأساليب العربية واستعمالها حسب السياق. ومن الملاحظ، قد تناول الكثير من الباحثين قضية ترجمة الآيات المتشابهات لأهميتها في معرفة معانيها في اللغة الهدف، غير أن دراستها من ناحية نظرية الترجمة الحديثة ما زالت قليلة. ومن هذا المنطلق، جاء هذا البحث الحالي ليسعى إلى دراسة هذه القضية من أجل تطبيق طريقتي الترجمة الحديثة، أوّلهما طريقة تحليل المكونات لنيومارك، والتي يتم من خلالها استخراج المعاني الموجودة من بنية الكلمات المتشابهات في القرآن الكريم وللتأكد من نجاعة معنى الترجمة، والثاني أساليب الترجمة لفيني وداربلني، والتي تهدف إلى بيان معرفة الأساليب المستخدمة من الترجمة المختارة. ومن ثم، يستخدم البحث المنهج النوعي بأسلوب تحليل النصوص لدراسة ترجمة الآيات المتشابهات لصفات الله معتمدًا على الترجمة المسماة بـ"تفسير فيمفينن الرحمن" للشيخ عبد الله باسميح بالتركيز على أربع كلمات متشابهات فقط وهي الوجه، والعين، والعلو، والإتيان أو المجيء. وأسفرت النتائج أن الترجمات المقدمة تتطابق مع المعاني المطلوبة لصفات الله غير أنها قد لا تتحقق المعنى المراد في بعض المواضع لعدم إظهار معاني الصفات بشكل كامل. أضف إلى ذلك، مال المترجم كذلك إلى الترجمة غير المباشرة خاصة لأسلوب التطويع للتناسب مع سياق النص، وكما أنه قام بزيادة بعض المعلومات في الهامش وبين قوسين سعيًا للوصول إلى تأكيد المعنى وتوضيحها بشكل أدق. ولذلك، أن ترجمة الآيات المتشابهات لصفات الله لا يمكن أن تقتصر  على الترجمة الحرفية فقط أو ما يقابلها أو يماثلها في اللغة الملايوية مما يسبّب بعض الخلل والنقائص، ولكن لا بد من التعامل معها بكل دقة وجدية بأهم المراجع وهي التفاسير من العلماء والمعاجم حتى تبدو مطابقة بمفهوم تنزيه الله عن الحوادث. Anthropomorphic verses (Mutasyᾱbihᾱt) that consist of Attributes of Allah are those verses which have many interpretations. Thus, the meaning of these verses must be interpreted based on the context that is equivalent to the attributes of Allah SWT according to the methods of Arabic language disciplines. Anthropomorphic verses and their translations into the target language are widely debated by researchers, but there are not many studies that concentrate on the context of modern translation theories. Thus, this study attempts to discover this issue using two main translation theories, firstly, Componential Analysis theory introduced by Newmark to explore the meaning provided for each anthropomorphic words and secondly by Vinay and Darbelnet theory that aims to examine the translation methods applied in the translation of anthropomorphic verses. This study employs a qualitative approach through text analysis method. Four anthropomorphic words were selected and elaborated descriptively: al-wajh, al-cain, al- culuw and al-ityān atau al-majī’. The Qur'an translation namely "Tafsir Pimpinan ar-Rahman" by Abdullah Basmeih serves as the study corpus. The findings shows that the anthropomorphic words are mostly translated in accordance with the exact meanings of Attributes of Allah as mentioned in the exegeses, but there are translations that did not describe the attributes of Allah clearly in certain places. It is also found that Abdullah Basmeih’s translation of the verses is inclined towards the oblique translation as to achieve equivalent meanings, as well as giving explanations in parentheses and footnotes in order to render the meaning of anthropomorphic words. Therefore, some implications were identified such as the translation of anthropomorphic verses should not be translated literally, but it should be referred to the Quranic exegeses and dictionaries so the intended meanings are appropriate to feature the attributes of Allah SWT. In conclusion, translators of the Qur’an must take into account appropriate translation methods in their translation process by referring to prominent exegeses.